2022
DOI: 10.1111/imj.15788
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐centre study on patients dying from COVID‐19: communication between clinicians, patients and their families

Abstract: Background COVID−19 has led to challenges in providing effective and timely communication in healthcare. Services have been required to adapt and evolve as successful communication remains core to high quality patient‐centred care. Aim This study aims to describe the communication between admitted patients, their families and clinicians (medical, nursing, allied health) during end‐of‐life care. Methods This retrospective review included all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…27 For HCWs, providing a link between patients and family increased their already heavy workload. 22 Harris et al described the workload for HCWs during COVID-19 as relentless and never-ending, and similar to our participants they faced limited opportunities to de-stress outside of work because of lockdown restrictions and social isolation. 28 This lack of 'breathing space' may lead to HCWs' struggling with breaking bad news, compounding the psychological impact of working on the COVID-19 frontline and result in HCWs' emotionally disengaging and/or feeling overwhelmed by feelings of guilt, sadness and anger.…”
Section: Main Findings Of the Studysupporting
confidence: 71%
See 1 more Smart Citation
“…27 For HCWs, providing a link between patients and family increased their already heavy workload. 22 Harris et al described the workload for HCWs during COVID-19 as relentless and never-ending, and similar to our participants they faced limited opportunities to de-stress outside of work because of lockdown restrictions and social isolation. 28 This lack of 'breathing space' may lead to HCWs' struggling with breaking bad news, compounding the psychological impact of working on the COVID-19 frontline and result in HCWs' emotionally disengaging and/or feeling overwhelmed by feelings of guilt, sadness and anger.…”
Section: Main Findings Of the Studysupporting
confidence: 71%
“…20,21 COVID-19 saw health facilities worldwide dealing with patients' suddenly facing an unpredictable illness, isolated in hospital and unable to see their family even when facing death. 22 The condition of patients could deteriorate and they could die suddenly without prolonged illness or warning, complicating discussions about prognosis, timelines and preparation for death. 23 It is reasonable to ask whether refusing to allow families to visit very ill patients was a rational or reasonable response by hospitals, given that PPE was available, and HCWs themselves were spending many hours in COVID facilities.…”
Section: Main Findings Of the Studymentioning
confidence: 99%
“…The importance of observing faith practices associated with death has been highlighted, with Muslim interviewees describing disenfranchised grief when death rituals and practices were disrupted by health protection measures ( Gabay & Tarabeih, 2022 ). The important role in communication that clinicians take on when visiting is restricted has been highlighted in a study which found that clinicians communicated more frequently with both patients and relatives the closer the patient was to death and often used video technology for these interactions ( Everitt et al, 2022 ). Lower levels of psychological distress have been found in people who were able to visit at the time of death and attend funerals ( Chen, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results were analyzed and compared using SPSS, APP Inventor, and mining models to determine application effects. (Chen, 2022) 4.4 Distribution of scientific production by area of knowledge In second place, Nursing with 125 articles and Social Sciences in third place with 14. The above can be explained thanks to the contribution and study of different branches, the article with the greatest impact was registered by the area of Medicine entitled "Effect of greater interprofessional familiarity on team performance, communication and psychological safety in medical teams of hospitalized patients: a randomized clinical trial" whose scope of study has as objective To determine the effectiveness of increasing familiarity between resident physicians and nurses on team performance, psychological safety and communication.…”
Section: Distribution Of Scientific Production By Year Of Publicationmentioning
confidence: 99%